Peran Divisi Food and Beverage (FnB) dalam Wastra Kencana – Indonesia Cultural Night Exhibition di Coventry: Strategi Kuliner dalam Diplomasi Budaya Indonesia Melalui Event Internasional - Raditha Sekar Kirani; Firman Syah; Karbala Madania; Noni Noerkaisar (Bisnis Event, 2026)
Wastra Kencana – Indonesia Cultural Night Exhibition is a cultural promotion event held by IISMA students in Coventry, United Kingdom. One of the key departments in this event was the Food and Beverage (FnB) Division, responsible for preparing and serving Indonesian traditional food and beverages to an international audience. This research aims to describe the role of the FnB Division in supporting the success of the event, covering the planning, execution, and evaluation phases. The study used a qualitative descriptive method through observation, interviews, and documentation. The results show that the FnB Division effectively fulfilled its duties with clear role division, adaptive sourcing of ingredients, and interactive service during the event. Challenges such as limited access to local ingredients and short preparation time were resolved through appropriate solutions. The FnB Division played a strategic role not only in supporting consumption logistics but also in promoting Indonesian culture through culinary diplomacy.